Autogenous vaccine therapy for condyloma acuminatum. A double-blind controlled study. Issue 1 (February 1982) - Malison, M D; Morris, R; Jones, L W
Abstract : In an attempt to substantiate claims that autogenous vaccine is an effective form of immunotherapy for condyloma acuminatum, a double-blind cross-over study was carried out on 34 patients, in which autogenous wart vaccine was compared with a placebo vaccine identically prepared from each patient's own normal skin. It was found that the duration of disease was an important determinant of curability in patients with condylomata acuminata (P less than 0.001) and that when this factor was taken into account autogenous wart vaccine was not significantly more effective than the placebo (P = 0.43).